Antifungal activity of novel synthetic peptides by accumulation of reactive oxygen species (ROS) and disruption of cell wall against Candida albicans - Maurya, Indresh Kumar; Pathak, Sarika; Sharma, Monika; Sanwal, Hina; Chaudhary, Preeti; Tupe, Santosh; Deshpande, Mukund V.; Chauhan, Virander Singh; Prasad, Rajendra (Peptides, 2011)
In the present work, we investigated the antifungal activity of two de novo designed, antimicrobial peptides VS2 and VS3, incorporating unnatural amino acid alpha,beta-dehydrophenylalanine (Delta Phe). We observed that the low-hemolytic peptides could irreversibly inhibit the growth of various Candida species and multidrug resistance strains at MIC(80) values ranging from 15.62 mu M to 250 mu M. Synergy experiments showed that MIC(80) of the peptides was drastically reduced in combination with an antifungal drug fluconazole. The dye PI uptake assay was used to demonstrate peptide induced cell membrane permeabilization. Intracellular localization of the FITC-labeled peptides in Candida albicans was studied by confocal microscopy and FACS. Killing kinetics, PI uptake assay, and the intracellular presence of FITC-peptides suggested that growth inhibition is not solely a consequence of increased membrane permeabilization. We showed that entry of the peptide in Candida cells resulted in accumulation of reactive oxygen species (ROS) leading to cell necrosis. Morphological alteration in Candida cells caused by the peptides was visualized by electron microscopy. We propose that de novo designed VS2 and VS3 peptides have multiple detrimental effects on target fungi, which ultimately result in cell wall disruption and killing. Therefore, these peptides represent a good template for further design and development as antifungal agents. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Antifungal peptides; Candida albicans; Cell wall; ROS

Molecular sieves and ultrasound-assisted synthesis of novel 1,3,4-oxadiazole-2-thiones derivatives as potential antifungal agents - Nikalje, Anna Pratima G.; Nimbalkar, Ms Urja D.; Tupe, Santosh; Vazquez, Julio A. Seijas; Tato, Maria Pilar Vazquez (19TH INTERNATIONAL ELECTRONIC CONFERENCE ON SYNTHETIC ORGANIC CHEMISTRY, 2015)
In the category of microorganism, fungi are considered as the special class of microbes responsible for opportunistic pathogenic infections in humans species. Due to the side effects of commercially available antifungal drugs and the emergence of new drug resistant fungal species in the past few years, has forced the researchers to search for novel and efficient antifungal drug molecules. The 1,3,4-oxadiazoles scaffold is associated with diverse biological activities. The multipurpose use of the Mannich bases in pharmaceutical chemistry promote us to prepare a new series of 5-(4-(benzyloxy)substituted phenyl)-3-((phenyl amino)methyl)-1,3,4oxadiazole-2(3H)-thione as antifungal agents. Herein, we report molecular sieves and ultrasound assisted synthesis of novel series of Mannich bases of the 5-substituted 1,3,4-oxadiazole-2-thiones by amino methylation with paraformaldehyde and substituted primary / secondary amines and their evaluation for antifungal activity. The structures of the newly synthesized compounds were determined by IR, NMR and Mass spectral study. The synthesized compounds exhibited interesting moderate to excellent antifungal activity against Candida albicans (NCIM 3557), Candida albicans(NCIM3471), Candida glabrata(NCIM3237), Cryptococcus neoformans (NCIM 3542), Cryptococcus neoformans(NCIM 3378), Aspergillus fumigates(NCIM 902), Aspergillus niger(NCIM 628) using Flucanazole as a standard reference drug. The synthesised compounds 6d, 6f,6g, 6h and 6j exhibited promising antifungal activity as antifungal agents.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular sieves; Ultrasound -assisted

Isolation and characterization of chitosans from different fungi with special emphasis on zygomycetous dimorphic fungus benjaminiella poitrasii: evaluation of its chitosan nanoparticles for the inhibition of human pathogenic fungi - Mane, Shamala; Pathan, Ejaj; Tupe, Santosh; Deshmukh, Sneha; Kale, Deepika; Ghormade, Vandana; Chaudhari, Bhushan; Deshpande, Mukund (Biomacromolecules, 2022)
The cell wall chitosan was extracted from fungi belonging to different taxonomic classes, namely, Benjaminiella poitrasii (Zygomycetes, dimorphic), Hanseniaspora guilliermondii, Issatchenkia orientalis, Pichia membranifaciens, and Saccharomyces cerevisiae (Ascomycetes, yeasts), and Agaricus bisporus and Pleurotus sajor-caju (Basidiomycetes). The maximum yield of chitosan was 60.89 ± 2.30 mg/g of dry mycelial biomass of B. poitrasii. The degree of deacetylation (DDA) of chitosan extracted from different fungi, as observed with 1H NMR, was in the range of 70–93%. B. poitrasii chitosan exhibited the highest DDA (92.78%). The characteristic absorption bands were observed at 3450, 1650, 1420, 1320, and 1035 cm–1 by FTIR. Compared to chitosan from marine sources (molecular weight, MW, 585 kDa), fungal chitosans showed lower MW (6.21–46.33 kDa). Further, to improve the efficacy of B. poitrasii chitosan (Bp), nanoparticles (Np) were synthesized using the ionic gelation method and characterized by dynamic light scattering (DLS). For yeast and hyphal chitosan nanoparticles (BpYCNp and BpHCNp), the average particle size was <200 nm with polydispersity index of 0.341 ± 0.03 and 0.388 ± 0.002, respectively, and the zeta potential values were 21.64 ± 0.34 and 24.48 ± 1.58 mV, respectively. The B. poitrasii chitosans and their nanoparticles were further evaluated for antifungal activity against human pathogenic Candida albicans ATCC 10231, Candida glabrata NCYC 388, Candida tropicalis ATCC 750, Cryptococcus neoformans ATCC 34664, and Aspergillus niger ATCC 10578. BpHCNps showed lower MIC90 values (0.025–0.4 mg/mL) than the chitosan polymer against the tested human pathogens. The study suggested that nanoformulation of fungal chitosan, which has low molecular weight and high % DDA, is desirable for antifungal applications against human pathogens. Moreover, chitosans as well as their nanoparticles were found to be hemocompatible and are therefore safe for healthcare applications.